Educational services quality monitoring system as an important component of library and archive management - Bachynska, Nadiia; Tverytnykova, Olena; Drozdova, Tetiana; Demidova, Yulia; Salata, Halyna (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article examines the hierarchical structure of the educational system as a component of library and archive management. It has been determined that the control system is structurally divided into three general levels: collection of information and stabilization of parameters, coordination of local subsystems of the first level, optimization of the control system. A study of the system for monitoring the quality of educational services in specialty 029 “Information, library and archival work” was carried out. The adequacy of the quality monitoring method has been experimentally proven. The object of testing was the procedure for assessing the quality of the educational process. The statistical array for checking the adequacy was taken from the results of the final control of the subjects of study from the examination sheets for individual parameters of the educational process.

У статті розглянуто ієрархічну структуру освітньої системи як складову бібліотечного та архівного менеджменту. Визначено, що система управління структурно поділяється на три узагальнені рівні: збір інформації та стабілізація параметрів, координація локальних підсистем першого рівня, оптимізація роботи системи управління. Проведено дослідження системи моніторингу якості освітніх послуг спеціальності 029 "Інформаційна, бібліотечна та архівна справа". Експериментально доведено адекватність методу моніторингу якості. Об'єктом апробації обрано процедуру оцінювання якості освітнього процесу. Статистичним масивом для перевірки адекватності було взято результати підсумкового контролю суб'єктів навчання з екзаменаційних відомостей за окремими параметрами навчального процесу.
Система моніторингу якості освітніх послуг як важлива складова бібліотечного та архівного менеджменту
Keywords: quality of education; monitoring; information technologies; management; archival activities; library and information activities; electronic resources; моніторинг якості освіти; архівна діяльністmь; бібліотечний менеджмент; електронні ресурси; інформаційні технології; освітні системи